Epidemiological Studies on Toxoplasmosis in Pregnant Women Using Serological Methods in Gezira State-Central Sudan - Elamin, Maha Hussein; Mohamedani, Ahmed Abdalla; Mohamed, Mohamed Elsanousi; Eljasir, Mai Hamad (Gezira Journal of Health Sciences; Vol 3 No 2 (2007), 2007)
Objective: To study the relationship between toxoplasmosis and the outcome of pregnancy (full term and abortion) and to find out the epidemiological risk factors. Methods: This case control study was carried out at Wad Medani Teaching hospital, Gezira State, Central Sudan during the period March 2002-May 2004. The cases were 100 pregnant women who presented with abortion between the second and fourth months of gestation, and the controls were 100 full term normally delivered women. Results: ELISA IgG test (n = 94 in each group) revealed 35.1% and 39.4% seroprevalence rates in the study and control groups respectively with no significant difference (p=0.6). When performed on IgG seropositives, ELISA IgM seroprevalence rates were 15.2% and 16.2%, in the study and control groups respectively. Statistically, there was no significant difference between them (p=0.9). When correlated to sociodemographic characteristics and risk factors, Toxoplsma gondii seroprevalence showed significant relationship for age, education, occupation, parity and past history of congenital malformations in both groups. There was significant difference between the two groups for ethnicity. The most important risk factor in both groups was the intake of raw meat (herbivorous viscera). Conclusion: The findings of this study suggests that, ingestion of infected raw meat is an important risk factor for toxoplasmosis. (OR, 3.87; 95%CI, 1.59-9.44) in the study group, while in the control group (OR, 4.41; 95%CI, 1.76-11.09).